2018
DOI: 10.1242/jeb.187559
|View full text |Cite
|
Sign up to set email alerts
|

Environmental temperature alters the digestive performance and gut microbiota of a terrestrial amphibian

Abstract: Environmental temperature and gut microbial communities can both have profound impacts on the digestive performance of ectothermic vertebrates. Additionally, the diversity, composition and function of gut microbial communities themselves are influenced by temperature. It is typically assumed that the temperature-dependent nature of ectotherm digestive performance is due to factors such as host physiological changes and adaptation to local climatic conditions. However, it is also possible that temperature-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 61 publications
4
128
0
Order By: Relevance
“…A similar effect has also been observed in tadpoles (Lithobates pipiens), which displayed decreases in relative abundances of Firmicutes at 28 • C relative to at 18 • C (Kohl and Yahn, 2016). The gut microbiotas of Salamanders (Plethodon cinereus) were also found to display progressive decreases in the relative abundances of genera within the Firmicutes (e.g., Anaerotrucus) at 10, 15, and 20 • C (Fontaine et al, 2018). In addition, laying hens exposed to heat stress have been shown to exhibit significant decreases in the relative abundance of Firmicutes within the fecal microbiota (Zhu et al, 2019).…”
Section: Experiments In Vertebratessupporting
confidence: 65%
See 1 more Smart Citation
“…A similar effect has also been observed in tadpoles (Lithobates pipiens), which displayed decreases in relative abundances of Firmicutes at 28 • C relative to at 18 • C (Kohl and Yahn, 2016). The gut microbiotas of Salamanders (Plethodon cinereus) were also found to display progressive decreases in the relative abundances of genera within the Firmicutes (e.g., Anaerotrucus) at 10, 15, and 20 • C (Fontaine et al, 2018). In addition, laying hens exposed to heat stress have been shown to exhibit significant decreases in the relative abundance of Firmicutes within the fecal microbiota (Zhu et al, 2019).…”
Section: Experiments In Vertebratessupporting
confidence: 65%
“…In mammals, Firmicutes and Bacteroidetes dominate, whereas Proteobacteria comprise a larger fraction of the gut microbiota in many birds, reptiles, and fish. Recent studies have assayed the gut microbiota of labreared or enclosure-reared vertebrates at different temperatures (Tajima et al, 2007;Chevalier et al, 2015;Kohl and Yahn, 2016;Bestion et al, 2017;Fontaine et al, 2018;Zhu et al, 2019). Despite the differences in composition among the gut microbiotas of vertebrate lineages, several general trends in responses of the gut microbiota to temperature variation have been observed across host species.…”
Section: Experiments In Vertebratesmentioning
confidence: 99%
“…Host diet is a primary environmental driver of microbiome variation in controlled laboratory studies 13,14 and humans 3 , and several studies in wild mammals have also demonstrated microbiome variation across spatial and seasonal ranges of nutritional variation. Other environmental factors that may interact with diet to influence the microbiome include altitude 20,21 and climate 22 . Host factors, such as genetic variation, have been shown to play a role in filtering particular microbes from the environment, thereby influencing the composition and relative abundances of resident microbial communities 23,24 .…”
mentioning
confidence: 99%
“…Staying in the PBT range optimizes multiple physiological functions (e.g. locomotion, digestion, development, reproduction) (Licht, 1965;Stevenson et al, 1985;Hertz et al, 1993;Navas and Bevier, 2001;Angilletta et al, 2002;Tracy et al, 2010;Berger et al, 2011;Fontaine et al, 2018). Heath's model also argues that when the environmental temperatures increase and the Tb of these organisms exceed their PBT range, they may present another type of behavioral response called "all-or-none".…”
Section: Introductionmentioning
confidence: 99%
“…The PBT optimizes multiple physiological functions (Licht, 1965;Heath, 1970;Stevenson, 1985;Hertz et al, 1993;Angilletta et al, 2002;Tracy et al, 2010), including locomotor performance (Bennet, 1990;Navas et al, 1999;Stevenson et al, 1985;Deere and Chown, 2006), feeding rates and digestive efficiency (Kingslover and Woods, 1997;Wang et al, 2002;McConnachie and Alexander, 2004;Fontaine et al, 2018), rates of development and growth (Berger et al, 2011) and reproduction (Navas and Bevier, 2001;Symes et al, 2017). However, when environmental conditions force the animal to an increase in Tb exceeding its PBT range, individuals may need to quickly retract from a thermally stressful situation to avoid prompt mortality.…”
Section: Introductionmentioning
confidence: 99%